Suscetibilidade geoambiental das terras secas da microrregião de Sobral Ce a desertlicação - Nolêto, Tânia Maria Serra de Jesus (2005)
The desertificação is a phenomenon that has occurred in dive rse parts of the world, what it took the ONU if to worry about its causes and expansion determining the areas that would be susceptible to the process. Irauçuba, integrant city of the Sobral’s Microregion is known as a Nucleus of Desertification in the half-barren Brazilian. The Sobral’s Microregion is distinguished in the State of the Ceará for its historical, educational and economic importance. With the purpose to evaluate the propagation of the desertificação in this area, a methodology based on the Climatic Index - IC was adopted, represented for the Index of Dryness - IA of the UNEP and the Index of Severity of Climate - ISC, gotten by Thornthwaite's method using the data collected in thirty and two rain ranks of the SUDENE in the historical series of 50 years. The Index of Erosion of Ground - IE S, represented for the Natural Potential of Erosion - IESN and for the Antropic Potential of Erosion - IESA, was determined by the use of the Universal Soil Loss Equation - EUPS, with the factors rain erosivity, soil erodibility, topographical component, vegetable cover and support practice, phenomenon caused for natural processes and activities human beings. The results allow to conclude that 80.10% of the territory are fit in susceptible areas to the process of desertification, demonstrated in Natural the Geoenvironmental Susceptibility - SGN and in the Antropic Geoenvironmental Susceptibility - SGA, in which the cities of Sobral, Miraíma and Irauçuba had presented a bigger susceptibility to the phenomenon.